Knocking down low molecular weight protein tyrosine phosphatase (LMW-PTP) reverts chemoresistance through inactivation of Src and Bcr-Abl proteins. - Paula A Ferreira (Public Library of Science (PLoS), 2012)
The development of multidrug resistance (MDR) limits the efficacy of continuous chemotherapeutic treatment in chronic myelogenous leukemia (CML). Low molecular weight protein tyrosine phosphatase (LMW-PTP) is up-regulated in several cancers and has been associated to poor prognosis. This prompted us to investigate the involvement of LMW-PTP in MDR. In this study, we investigated the role of LMW-PTP in a chemoresistant CML cell line, Lucena-1. Our results showed that LMW-PTP is highly expressed and 7-fold more active in Lucena-1 cells compared to K562 cells, the non-resistant cell line. Knocking down LMW-PTP in Lucena-1 cells reverted chemoresistance to vincristine and imatinib mesylate, followed by a decrease of Src and Bcr-Abl phosphorylation at the activating sites, inactivating both kinases. On the other hand, overexpression of LMW-PTP in K562 cells led to chemoresistance to vincristine. Our findings describe, for the first time, that LMW-PTP cooperates with MDR phenotype, at least in part, through maintaining Src and Bcr-Abl kinases in more active statuses. These findings suggest that inhibition of LMW-PTP may be a useful strategy for the development of therapies for multidrug resistant CML.